SEISMOGENIC SOURCES IN THE AEGEAN AREA AND THEIR PREDICTIVE PROPERTIES - Papazachos, B.C.; Karakaisis, G.F.; Scordilis, E.M.; Papaioannou, Ch. (Bulletin of the Geological Society of Greece, 2016)
On the basis of all available information eight circular seismogenic sources, where shallow (h 100km) earthquakes occur, are defined in the broader Aegean area. The location of each source is further improved by optimization of the quasi-periodic properties of the strong (M≥6.0) instrumentally recorded mainshocks, identified in a complete catalogue of earthquakes (1911-2014) after declustering. Moreover, in the same seismogenic sources, all M≥6.3 mainshocks that comprise another complete catalogue (1850-2014) have also occurred. Interevent times of mainshocks generated in each source have predictive properties expressed by the TIMAPR (Time and Magnitude Predictable Regional) model whereas preshocks of recent mainshocks have also such properties expressed by the D-AS (Decelerating-Accelerating Seismicity) model. Retrospective prediction of the last mainshock in each source by the joint application of the two models resulted in reasonable uncertainties. Then, as a forward test, data up to the end of 2014 were used to predict the next expected mainshock in each of the eight sources and to identify the fault where its epicentre will probably be located.